1986
DOI: 10.1111/j.1365-2389.1986.tb00011.x
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium accumulation in soils from long‐continued applications of superphosphate

Abstract: A simple, sensitive method developed for the analysis of geostandards was used to measure the accumulation of Cd in soils from superphosphate applied annually to grassland and arable soils for many years. Rates of application were equivalent to 33 kg P and 5 g Cd ha-' yr-' for 95 yr in three experiments in England and to 37 kgP and 20gCdha-'yr-' for 30 yr in one experiment in New Zealand. Very little Cd accumulated in the surface horizons (0-22.5cm) of either of the arable soils from England; about one-quarter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(41 citation statements)
references
References 13 publications
1
39
0
1
Order By: Relevance
“…On the contrary, another factor that would explain low Cd accumulation in Chillán for grain, stem, and root could be due to greater competition between the H + and Cd +2 cations in the uptake sites on the root surface (Larsson and Asp, 2013). A directly proportional response was found between the applied Cd rate and root Cd concentration ( Figure 2b); results were similar to those reported by Liu et al (2013), and values corresponded to an increase equivalent to 3.5 and 4.5 times compared with the control when applying 1 and 2 mg kg (Rothbaum et al, 1986;Quezada-Hinojosa et al, 2015) (Figures 3a, 3b, 3c), and also similar to those cited by Segura et al (2006) for different soils in…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…On the contrary, another factor that would explain low Cd accumulation in Chillán for grain, stem, and root could be due to greater competition between the H + and Cd +2 cations in the uptake sites on the root surface (Larsson and Asp, 2013). A directly proportional response was found between the applied Cd rate and root Cd concentration ( Figure 2b); results were similar to those reported by Liu et al (2013), and values corresponded to an increase equivalent to 3.5 and 4.5 times compared with the control when applying 1 and 2 mg kg (Rothbaum et al, 1986;Quezada-Hinojosa et al, 2015) (Figures 3a, 3b, 3c), and also similar to those cited by Segura et al (2006) for different soils in…”
Section: Discussionsupporting
confidence: 77%
“…However, concentrations and the magnitude of the differences were lower (Figures 3a, 3b). This effect could be attributable to the characteristics of this element in the soil, which is mainly located at the surface (Rothbaum et al, 1986). When comparing the environments, the Cd concentration was higher in Los…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One such farming practice that is a likely source of Cd is the application of phosphatic fertilisers. Reports in the literature (Williams & David 1973;Williams & David 1976;Rothbaum et al 1986) have shown that soil Cd concentration and the amount of superphosphate added were strongly related. Mortvedt (1987) has shown that accumulation of Cd in soils was negligible when Cd in the fertiliser was less than 10 (ig/g, whereas Andersson (1976) calculated that if Cd concentration in fertiliser exceeded 8 (lg/g, topsoil Cd levels were likely to increase.…”
Section: Introductionmentioning
confidence: 99%
“…Mortvedt (1987) has shown that accumulation of Cd in soils was negligible when Cd in the fertiliser was less than 10 (ig/g, whereas Andersson (1976) calculated that if Cd concentration in fertiliser exceeded 8 (lg/g, topsoil Cd levels were likely to increase. Australian superphosphate has been shown to contain, on average, 33 jig Cd/g (range 6-68 ng/g) (Hilliard et al 1988) whereas New Zealand superphosphate contained, on average, 48 ug Cd/g (range 34-69 ug/g) (Rothbaum et al 1986). The Cd in superphosphate arises primarily from the phosphorite used as the raw material, although Cd content varies considerably with origin of the phosphorite (Syers et al 1986).…”
Section: Introductionmentioning
confidence: 99%